Sounds can boost the awareness of visual events through attention without cross-modal integration - Pápai, Márta Szabina (Sci Rep, 2017)
Cross-modal interactions can lead to enhancement of visual perception, even for visual events below awareness. However, the underlying mechanism is still unclear. Can purely bottom-up cross-modal integration break through the threshold of awareness? We used a binocular rivalry paradigm to measure perceptual switches after brief flashes or sounds which, sometimes, co-occurred. When flashes at the suppressed eye coincided with sounds, perceptual switches occurred the earliest. Yet, contrary to the hypothesis of cross-modal integration, this facilitation never surpassed the assumption of probability summation of independent sensory signals. A follow-up experiment replicated the same pattern of results using silent gaps embedded in continuous noise, instead of sounds. This manipulation should weaken putative sound-flash integration, although keep them salient as bottom-up attention cues. Additional results showed that spatial congruency between flashes and sounds did not determine the effectiveness of cross-modal facilitation, which was again not better than probability summation. Thus, the present findings fail to fully support the hypothesis of bottom-up cross-modal integration, above and beyond the independent contribution of two transient signals, as an account for cross-modal enhancement of visual events below level of awareness.